The Dental Arch Chances In Extractıon And Non-Extractıon Treatment - Meliha Rübendüz; Sonay Altunay (Galenos Yayinevi, 2001)
The aim of this study was to evaluate the treatment changes in dental arches of dental and skeletal Class I. extraction and non-extraction cases, comparatively For this aim. pretreatment and posttreatment orthodontic casts and lateral cephalometric films of 24 dental and skeletal Class 1 females were used in this study. The first group consisted of 12 females who were treated with four first premolar extractions. The second group consisted of 12 females who were treated with non-extraction method. All of the subjects in both groups were pre-selected according to their correspondence of ANB. GoGn-SN, overbite and overjet values. The ages of the subjects were 12 and over. Subjects in both groups had moderate dental crowding. Eight dimensional, 2 proportional measurements were done in dental casts of the subjects. It was found that maxillary intercanine dimension decreased while mandibular intercanine dimension increased in both groups. Maxillary intermolar dimension increased in the non-extraction group while a decrease was found in the extraction group. Also mandibular intermolar dimension decreased in the extraction group and obviously increased in the non-extraction group.